Hypoxia‐Inducible Factor‐2α Reprograms Liver Macrophages to Protect Against Acute Liver Injury Through the Production of Interleukin‐6. Issue 6 (4th February 2020) - Gao, Rachel Y.; Wang, Meng; Liu, Qihui; Feng, Dechun; Wen, Yankai; Xia, Yang; Colgan, Sean P.; Eltzschig, Holger K.; Ju, Cynthia
Abstract : Background and Aims: Acetaminophen (APAP) overdose represents the most frequent cause of acute liver failure, resulting in death or liver transplantation in more than one third of patients in the United States. The effectiveness of the only antidote, N ‐acetylcysteine, declines rapidly after APAP ingestion, long before patients are admitted to the clinic with symptoms of severe liver injury. The direct hepatotoxicity of APAP triggers a cascade of innate immune responses that may exacerbate or limit the progression of tissue damage. A better understanding of this complex mechanism will help uncover targets for therapeutic interventions. Approach and Results: We observed that APAP challenge caused stabilization of hypoxia‐inducible factors (HIFs) in the liver and hepatic macrophages (MΦs), particularly HIF‐2α. Genetic deletion of the HIF‐2α gene in myeloid cells (HIF‐2α mye/− ) markedly exacerbated APAP‐induced liver injury (AILI) without affecting APAP bioactivation and detoxification. In contrast, hepatic and serum levels of the hepatoprotective cytokine interleukin 6 (IL‐6), its downstream signal transducer and transcription factor 3 activation in hepatocytes, as well as hepatic MΦ IL‐6 expression were markedly reduced in HIF‐2α mye/− mice compared to wild‐type mice post‐APAP challenge. In vitro experiments revealed that hypoxia induced IL‐6 production in hepatic MΦs and that such induction was abolished in HIF‐2α‐deleted hepatic MΦs. Restoration of IL‐6 by administration of exogenous IL‐6 ameliorated AILI in HIF‐2α mye/− mice. Finally, IL‐6‐mediated hepatoprotection against AILI was abolished in hepatocyte‐specific IL‐6 receptor knockout mice. Conclusions: The data demonstrate that APAP treatment leads to HIF‐2α stabilization in hepatic MΦs and that HIF‐2α subsequently reprograms hepatic MΦs to produce the hepatoprotective cytokine IL‐6, thereby ameliorating AILI.